(untitled) (Global Journal of Medical Research, 2021)
Background: Two years ago the Coronavirus disease 2019 was identified in Wuhan, China for the first time in December 2019 and since then it has unfolded throughout the globe inflicting the worldwide collapse and closure of international borders, health care facilities as well as disrupt all social activities. One in every of the area’s that has been adversely affected is the health care system. The forceful results of Covid-19 on health care systems is overshadowed by its effect on economic activities, that has been put on attentiveness of many news platforms and media retailers. This has ensued very little or no applied statistical data on the various health care staff that have been and still being lost t Covid-19 pandermic.